(untitled) (Seven Editora, 2025)
Science is a field of knowledge in which different disciplines intertwine to form a greater whole. Science and Connections: The Interdependence of Disciplines is a book that extends this interconnection, bringing together more than 200 articles on various topics, written by experts from different fields of knowledge. Developed by Seven Publications, this book presents a broad overview of the challenges, discoveries and advances in fields such as health, technology, biology, physics, psychology, philosophy and much more. Link: https://www.sevenpubli.com/livro/science-and-connections-the-interdependence-of-disciplines